Manajemen Penyelenggaraan Haji dan Umroh Pada Wilayah Kementerian Agama Provinsi Sulawesi Tengah - M, Rudin; Bakarbessy, Maria Lea Frensy; Pakere, Rusli Andrian (Jurnal Manajemen STIE Muhammadiyah Palopo, 2025)
Abstract The aim of this study is to analyze the management of Hajj and Umrah services at the Ministry of Religious Affairs Regional Office in Central Sulawesi Province. This research employs a qualitative approach with four purposively selected informants. Data collection was carried out through observation, interviews, and documentation techniques. Data analysis was conducted in five steps: data collection, data reduction, data presentation, verification, and conclusion drawing. The results indicate that the management of Hajj and Umrah services at the Ministry of Religious Affairs Regional Office in Central Sulawesi Province has not been optimally implemented. The inhibiting factors identified include inadequate SISKOHAT network for online registration, administrative services not meeting the established standards, insufficient effective communication with the public, and a shortage of personnel in providing services to Hajj and Umrah pilgrims during departure. The supporting factors that facilitate the management process include adequate facilities and infrastructure, experienced Hajj and Umrah instructors, professional staff in pilgrim services, and available funding to support the office’s operations. Keywords: Management, Hajj and Umrah.Abstrak Tujuan dari penelitian ini adalah untuk menganalisis manajemen penyelenggaraan haji dan umroh pada Kantor Wilayah Kementerian Agama Provinsi Sulawesi Tengah. Penelitian ini menggunakan pendekatan kualitatif dengan empat informan yang dipilih secara purposive. Pengumpulan data dilakukan melalui teknik observasi, wawancara, dan dokumentasi. Analisis data dilakukan dengan lima langkah, yaitu pengumpulan data, reduksi data, penyajian data, verifikasi, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa manajemen penyelenggaraan haji dan umroh pada Kantor Wilayah Kementerian Agama Provinsi Sulawesi Tengah belum berjalan dengan optimal. Faktor penghambat yang ditemukan antara lain jaringan SISKOHAT yang tidak memadai untuk pendaftaran online, pelayanan administrasi yang tidak sesuai dengan standar yang ditetapkan, kurangnya komunikasi efektif dengan masyarakat, dan kekurangan jumlah petugas dalam pelayanan jamaah haji dan umroh pada saat pemberangkatan. Adapun faktor pendukung yang memperlancar manajemen ini adalah sarana dan prasarana yang memadai, pembimbing manasik haji dan umroh yang berpengalaman, tenaga ahli profesional dalam pelayanan jamaah, dan dana yang tersedia untuk mendukung operasional kantor. Kata Kunci: Manajemen, Haji dan Umroh.